Monoclonal antibody 18B8 detects gangliosides associated with neuronal differentiation and synapse formation. - Grunwald, G B (1985)
Mouse monoclonal antibody 18B8 detects developmentally regulated antigens in chicken retina and brain. The antigens detected by immunofluorescence appear initially on cell bodies in retinas of 6-13 day embryos. In older embryos during synapse formation and in adults, the antigen is localized in discrete laminae within the inner synaptic layer of retina and also is present in the outer synaptic layer and the outer segments of photoreceptor cells. The antigens from retina and brain were purified partially and were shown to be gangliosides of unknown structure that contain at least two sialic acid residues. Gangliosides that are recognized by antibody 18B8 change both qualitatively and quantitatively during neuronal development. These changes were correlated with the spatial and temporal changes in antigen expression detected histochemically.